Surveillance of nosocomial infections in a Mexican community hospital: how are we doing? Vigilancia epidemiológica de infecciones nosocomiales en un hospital comunitario de México: ¿Cómo vamos? - Lourdes García-García; María-Eugenia J; Laura-Elizabeth R; Renata Báez-Saldaña; Leticia Ferreyra-Reyes; Elizabeth Ferreira-Guerrero; Bulmaro Cano-Arellano; Pablo Cruz-Hervert; Norma Araceli Téllez-Vázquez; Leonardo Verduzco-Rodríguez; Yolanda Jaramillo-Cosme; Eleazar Luna-Téllez; et al. (Instituto Nacional de Salud Pública, 2010)
OBJECTIVE. To compare the nosocomial infection (NI) rate obtained from a retrospective review of clinical charts with that from the routine nosocomial infection surveillance system in a community hospital. MATERIAL AND METHODS. Retrospective review of a randomized sample of clinical charts.Results were compared to standard surveillance using crude and adjusted analyses. RESULTS. A total of 440 discharges were reviewed, there were 27 episodes of NIs among 22 patients. Cumulated incidence was 6.13 NI per 100 discharges. Diarrhea, pneumonia and peritonitis were the most common infections. Predictors of NI by Cox regression analysis included pleural catheter (HR 16.38), entry through the emergency ward, hospitalization in the intensive care unit (HR 7.19), and placement of orotracheal tube (HR 5.54). CONCLUSIONS. Frequency of NIs in this community hospital was high and underestimated. We identified urgent needs in the areas of training and monitoring. OBJETIVO. Comparar la tasa de infecciones nosocomiales (IN) resultante de la revisión retrospectiva de expedientes clínicos con los resultados del sistema rutinario de vigilancia de IN de un hospital general. MATERIAL Y MÉTODOS. Revisión retrospectiva de una muestra seleccionada aleatoriamente de expedientes clínicos. Comparación con los resultados obtenidos por el sistema rutinario de vigilancia de IN. Análisis bivariado y multivariado de datos retrospectivos. RESULTADOS. De 440 egresos hubo 27 episodios de IN en 22 pacientes. La incidencia acumulada fue de 6.13 IN por 100 egresos. Las infecciones más frecuentes fueron diarrea, neumonía y peritonitis. Los predictores de IN fueron catéter pleural (HR 16.38), ingreso por urgencias y estancia en cuidados intensivos (HR 7.19), y colocación de tubo orotraqueal (HR 5.54). CONCLUSIONES. La frecuencia de IN fue elevada y subestimada por el sistema rutinario. Identificamos necesidades urgentes de monitoreo y entrenamiento en áreas específicas.